2012
DOI: 10.4172/2161-0444.1000114
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Cytokines for Mucosal Immunity Induced By Dietary Vanadium in the Intestine of Broilers

Abstract: Cytokines are key regulators of the immune system that shapes both the innate and adaptive immune responses. Present knowledge allows a deeper understanding of the cytokine network and their complex roles in the development of immune responses. The purpose of this study was to examine the effect of dietary vanadium on the contents of cytokines such as interleukin-2 (IL-2), interleukin-6 (IL-6), interleukin-10 (IL-10), interferon gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α) in the mucosa of different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The immunotoxicity of vanadate has been proved [13]. At the same time, the results of our recent studies have shown that high levels of dietary vanadium can cause the lesions in lymphoid organs, inhibit the growth of lymphoid organs, splenic oxidative stress and splenocyte apoptosis, and affect the secretion of immunologic factors and cytokine contents in the mucosal immunity of broilers [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The immunotoxicity of vanadate has been proved [13]. At the same time, the results of our recent studies have shown that high levels of dietary vanadium can cause the lesions in lymphoid organs, inhibit the growth of lymphoid organs, splenic oxidative stress and splenocyte apoptosis, and affect the secretion of immunologic factors and cytokine contents in the mucosal immunity of broilers [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%